Control optimization of dual active bridge converter for DC microgrids with reduced DC-bus capacitance - Lee, Chun Meng (Nanyang Technological University, 2020)
Power electronic converters are widely used in common electronic devices such as computers, mobile phones, television, etc. Through conversion techniques, methods in the power electronic converters are programmed to process and control electrical energy by transforming it into various forms to fulfil the end-user requirements.